Poetic transformations : eighteenth-century cultural projects on the Mekong plains - Ang, Claudine, 1976- (Harvard East Asian monographs ;, 2019)
"In the eighteenth century, the Mekong plains were the site of convergence of multiple migratory groups with competing political ambitions. Drawing on Vietnamese and Chinese sources, this study identifies the ways in which two leading statesmen mobilized literature to effect the transformation of the frontier region"--